2012
DOI: 10.1155/2012/795958
|View full text |Cite
|
Sign up to set email alerts
|

BothCD4+andCD8+Lymphocytes Participate in the IFN-γ Response to Filamentous Hemagglutinin fromBordetella pertussisin Infants, Children, and Adults

Abstract: Infant CD4+T-cell responses to bacterial infections or vaccines have been extensively studied, whereas studies on CD8+T-cell responses focused mainly on viral and intracellular parasite infections. Here we investigated CD8+T-cell responses uponBordetella pertussisinfection in infants, children, and adults and pertussis vaccination in infants. Filamentous hemagglutinin-specific IFN-γsecre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 50 publications
2
15
0
1
Order By: Relevance
“…Our results, showing a clear proliferation of CD4 ϩ and CD8 ϩ T cells of aP-primed children upon pertussis stimulation, are in agreement with studies that showed that CD4 ϩ and CD8 ϩ T cells are involved in the immune response against pertussis (13,21,23). Moreover, the observations that pertussis-specific T CM were more prevalent in CD4 ϩ than in CD8 ϩ T cells and that the relative proportions of T CM and T EM do not change after a booster immunization are in line with other studies on memory T-cell subsets (16,24).…”
Section: Discussionsupporting
confidence: 92%
“…Our results, showing a clear proliferation of CD4 ϩ and CD8 ϩ T cells of aP-primed children upon pertussis stimulation, are in agreement with studies that showed that CD4 ϩ and CD8 ϩ T cells are involved in the immune response against pertussis (13,21,23). Moreover, the observations that pertussis-specific T CM were more prevalent in CD4 ϩ than in CD8 ϩ T cells and that the relative proportions of T CM and T EM do not change after a booster immunization are in line with other studies on memory T-cell subsets (16,24).…”
Section: Discussionsupporting
confidence: 92%
“…There are, however, no reports yet on the role of Tc17 during B. pertussis infection. Although CD8 + T cells were found to be dispensable for resolving B. pertussis infection in the mouse model [22], [23], in humans IFN-γ producing CD8 + T cell responses were detected in a cohort of B. pertussis -infected infants and young adults, as well as in vaccinated children [24]. It remains, hence, to be determined whether these cells are induced by the adjuvant activity of B. pertussis virulence factors, or whether CD8 + T cells actively participate in host defense against B. pertussis .…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the breadth of the responses induced by natural infection versus the different vaccine constructs, epitope data were defined from a relatively small number of B. pertussis antigens (6 of >3400). The majority of epitopes were defined for PT, and far fewer were reported for antigens incorporated within currently licensed aP vaccines, and also associated with vaccine-induced immunity and in immunity to natural infection [11,49–51]. Thus a meaningful assessment of how the epitope breadth elicited by natural infection versus aP and wP vaccination could not be undertaken.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Numerous studies published to date have demonstrated a role for T cells/cell-mediated immunity following immunization and natural infection [11,49,50,60–62]. Despite this, very little of the T cell epitope data were characterized phenotypically.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation